Обеспечение испытаний бортовых блоков управления стартерами-генераторами - Буряченко, Анна Григорьевна; Царев, Андрей Анатольевич (Avìacìjno-kosmìčna tehnìka ì tehnologìâ, 2021)
There are described the results of the creation by the developer of the on-board equipment – JSC "Element" – improved specialized test equipment for checking the parameters of the on-board control units of DC starter-generators – a stand-simulator of the starter-generator. The previously developed version improvement was carried out to increase the tests automatization because of preparation for control units' serial production stage. In addition, during the improvement process, the list of simulated starter-generators has been expanded, namely, to the starter-generators produced in France (THALES), Russia (STG9M-1, STG-3), and Ukraine (8260-12UD, 8260-9UD, STG-150UD) for the AI-450M engine and its modifications (with which the BZG-450 unit worked, providing control of start-up and generation) the STG-12TMO-1000 starter-generator was added. This STG-12TMO-1000 works with the AI-25TLT engine, for which Element JSC is currently developing an SGU-25 unit for control of start-up and generation. Stand-simulator improvement was based on an additional experimental study of the interaction between mentioned control units and real objects. The interaction was studied during the test process on the engine stand and aircraft of the State Enterprise "Ivchenko-Progress" and JSC "Motor Sich". The results achieved are shown. There are shown the structural diagram of improved stand-simulator and working screen of specialized software installed on a personal computer and providing the operator with the ability to control the test process. A list of simulated analog and frequency signals with ranges and errors indication is given. In addition to the stand-simulator description, attention is also paid to the quality checking method of the installation of printed circuit boards of control units by thermography means under electrical load and comparison with a specially prepared reference picture of temperature distribution. The need for such especially careful control during acceptance tests is due to the level of flowing currents – up to 20 A.